Clinico-Laboratory Profile And Drug Sensitivity Pattern In Urinary Tract Infection Of Children In A Tertiary Care Hospital - Bilal, Muhammad; Nadeem , Muhammad Tariq; Adnan; Jalal, Abdul; Ahmad , Ishfaq; Samad, Abdul (Journal of Rawalpindi Medical College, 2023)
Background: Any component of the urinary system can get infected with bacteria, which is known as a urinary tract infection (UTI). It is one of the most common bacterial diseases in children. The study’s objectives included identifying the clinical symptoms of UTI in children between the ages of one month and fifteen, as well as the bacteria responsible for the illness and their sensitivity to various medicines. Methods: This cross-sectional study was conducted at the CMH Rawalpindi, Pakistan, from January to June of 2022. Our analysis comprised 137 strongly suspected instances of UTI in children (1 month to 15 years old). Results: A total of 137 urine samples from paediatric patients suspected of having UTI were obtained in which the 93 samples (67.88%) generated significant bacteria. The two most common clinical symptoms of UTI patients in our research were fever and dysuria. E. coli was the most prevalent isolate in cases with paediatric UTI. Ampicillin, cephalosporins, and co-trimoxazole were the medications that were most effective against E. coli and Klebsiella, respectively. Conclusions: The age range between 1 and 5 years old was the one most usually affected by UTI. We must be aware of the need of doing a urine culture sensitivity test before to starting antimicrobial medicine in order to detect UTI early, avoid recurrent UTI, and reduce paediatric morbidity and mortality.